Humans in the perfectly competitive market - Karine Nyborg (University of Oslo, Department of Economics, 2019)
The perfectly competitive market - a hypothetical situation free of market failure - serves as a benchmark for economic theory, providing the basis for the two fundamental welfare theorems. The radical abstractions of this idea makes it hard to grasp its full implications, however. In this essay, I explore the perfectly competitive market using literary fiction. Part I discusses fiction as a tool for economic theory. Part II is a science fiction story about two economists travelling to the perfectly competitive market for their honeymoon. Part III develops main theoretical insights emerging from the story. First, to preclude market failure, complete social isolation must prevail. Second, the requirements of symmetric information and no external effects are extremely hard to reconcile, leading to an impossibility result: if trade is permitted anytime, and deliberate, welfare-relevant learning is feasible, no perfectly competitive market can exist.
Keywords: A11; A12; B49; D5; D60; D62; D82; 330; Welfare theorems; narratives; social interaction; symmetric information; complete contracts